FACTORS INFLUENCING STUDENTS’ PERCEPTIONS OF TAX EVASION - Nuri Annisa Fitri; Basri, Hisbullah; Arifin, Firmansyah (Universitas Muhammadiyah Bengkulu, 2025)
This study aims to determine and analyze how Tax Sanctions and Justice affect Student Perceptions of Tax Evasion. This study has two independent variables, namely tax sanctions and tax justice and one dependent variable, namely student perceptions of tax evasion. The population in this study were active students at the Faculty of Economics and Business, Tridinanti University. S1 Accounting Study Program, S1 Management and D3 Finance and Banking. The sample in this study was determined by using the convenience sampling technique, meaning that the sample was selected based on the ease of obtaining data. The number of samples in this study was 128 people. The research data is in the form of primary data in the form of a questionnaire. The questionnaire was distributed online to students via google form. The results of the questionnaire were processed using IBM SPSS Statistics 20 software. Based on the results of the hypothesis test, it can be said that the first hypothesis, the t-test sig. value is 0.034 <0.05. This means that the independent variable of tax sanctions (X1) has a significant effect on the dependent variable of tax evasion (Y). The second hypothesis, the t-test sig. value is 0.001 < 0.05. This means that the independent variable of tax justice (X2) has a significant effect on the dependent variable of tax evasion (Y). The third hypothesis, the sig. F value is 0.000 < 0.05. This means that tax sanctions and tax justice have an effect on tax evasion